Strategi Layanan Bimbingan dan Konseling dalam Membentuk Penanaman Minat Pembelajaran Sebagai Upaya Mencegah Pengangguran di SMK Bhakti Kencana Pangandaran - Lulu Andiani; Dela Zahara; Nurafilah Febriyanti; Widayanti Widayanti (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2024)
This research aims to explore strategies for guidance and counseling services in cultivating an interest in learning that can be effective in preventing unemployment at SMK Bhakti Kencana Pangandaran. This research method uses a qualitative approach with a descriptive approach. The results of the study found that the most effective strategy in minimizing poverty and unemployment in Indonesia is held by educational institutions that guide students to gain skills in getting jobs. Supporting the success of the strategy depends on two factors, namely educators and students in achieving learning. Therefore, educators must provide trial classes and hold MOUs with companies, on the other hand, students must be consistent with the learning they are interested in.